Middle East and North Africa Regional Economic Update, April 2014 : Harnessing the Global Recovery - A Tough Road Ahead - Devarajan, Shantayanan; Mottaghi, Lili (Washington, DC: World Bank, 2014)
Compared with the previous three years, 2014 seems hopeful and 2015 could be a turning point for the countries in the Middle East and North Africa (MENA) region. Many countries in MENA will start to benefit from stronger external demand in the high-income economies, as the global economy is set for a rebound in 2014. In the MENA region, higher global demand is expected to boost exports of energy and manufactured products in those countries that have trade linkages with high- income countries. Growth in MENA is expected to reach 3.3 percent in 2014 and further accelerate to 4.6 percent in 2015. Nevertheless, the prospects for growth in MENA could be threatened if long awaited structural problems remain unresolved.